SYSTEMATIC LITERATUR REVIEW : KEMAMPUAN BERPIKIR KREATIF SISWA DALAM PEMBELAJARAN GEOMETRI - Sahira, Adinda; Sari, Rika Mulyati Mustika; Effendi, Kiki Nia Sania (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
Creative thinking skills are the ability to communicate ideas, solve problems, and create something that has never been discovered by others. Geometry is one of the areas of mathematics taught in schools that requires the use of reasoning, calculation analysis, and creative imagination. This study aims to review the literature on the topic of creative thinking skills in geometry learning in junior high school. SLR (Systematic Literature Review) on “Creative Thinking Ability” and “Geometry” that have been published in the last ten years served as the research methodology. Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), which generates research articles for systematic reviews between 2014 and 2024, became the basis of this study. The results show that there are several levels of creative thinking skills in geometry learning, namely high, medium, and low, using various approaches, models, and media support. Through the use of media and problem development tools, the results showed a high level of creative thinking ability. A moderate level was achieved when students only showed one or two of the three previously mentioned indicators of creative thinking ability, or when they had not fully met the indicators. The low level was achieved when students did not meet any of the creative thinking indicators and were mostly directed by teacher examples or standard working procedures without any input from students on how to solve the problem